Studying Demographic And Clinical Pattern In Contemporary Prospective Of Atopicdermatitis - Mr. Dipanshu Garg, Dr. Sailesh Narayan (Drugs and Cell Therapies in Hematology, 2021)
An atopic dermatitis (AD) is a common, chronic skin illness that can have a substantial influence on the affected persons’ and their families’ quality of life. Pathogenesis of this condition is not fully understood although it appears to be a complicated interaction between skin barrier dysfunction, environmental and infectious agents as well as immunological abnormalities. On the basis of established three or more major and minor criteria, conspicuous presentations of atopic dermatitis were documented in a pre-set proforma, which also noted age, duration of the disease and gender. The results were presented in this study. End result: Atopic dermatitis is an overt, age-related IgE-related phenomenon that has a wide range of demographic and clinical implications.